The effects of 8 weeks of sprint interval training on repeated sprinting and specialized ability in college volleyball players - Wei, C.; An, J.; Zhou, L. (PLOS ONE, 2025)
Objective This study aimed to investigate the effects of 8 weeks of sprint interval training (SIT) on repeated sprinting ability and specialized performance in collegiate volleyball players.